Creative self-efficacy as mediator and cultural context as moderator in empowerment, mindset, and creative behavior - Nurfaizal, Yusmedi; Barros, Agapito (Jurnal Fokus Manajemen Bisnis, 2025)
Creativity is increasingly recognized as a vital skill in digital education, influenced by both psychological and sociocultural factors. This study investigates how psychological empowerment and growth mindset influence creative behavior among digital business students, examining creative self-efficacy as a mediator and cultural context (individualism vs. collectivism) as a moderator. Using stratified proportional random sampling, data were collected from 100 students at Universitas Amikom Purwokerto and analyzed through Partial Least Squares Structural Equation Modeling with Smart PLS version 4. Results reveal that psychological empowerment and growth mindset both directly and indirectly enhance creative behavior via creative self-efficacy. Creative self-efficacy emerges as a significant mediating mechanism that amplifies these effects. Furthermore, cultural context moderates the model, with stronger pathways observed in individualistic cultures. These findings underscore the importance of nurturing self-efficacy and mindset within supportive and culturally responsive environments to foster student creativity. Theoretically, this study advances social cognitive theory, self-determination theory, and growth mindset theory by clarifying the joint influence of psychological and cultural factors. Practically, it suggests that creativity development programs centered on empowerment and mindset cultivation should be adapted to fit cultural orientations. This research offers a robust foundation for future investigations into creativity’s psychological and sociocultural antecedents in digital learning contexts.